Response of Goat Fed with Indigofera sp. and Pennisetum purpureum cv. Mott - Kaunang Charles L.; Lomboan Agustinus; Pudjihastuti Endang (BIO Web of Conferences, 2024)
This study evaluated the response of goat fed with Indigofera Sp. and Pennisetum purpureum cv. Mott. We randomly assigned fifteen goats with an initial body weight of ±20 kg into three treatments and five replications using Completely Randomized Design (CRD). The treatments were T0= 0% Indigofera sp. + 100% Pennisetum purpureum cv. Mott T1 = 20% Indigofera sp. + 80% Pennisetum purpureum cv. Mott, T2= 40% Indigofera sp. + 60% Pennisetum purpureum cv. Mott. Data analysis was done with analysis of variance (ANOVA) test and Duncan multiple range test. We assessed daily weight gain, dry matter intake, digestibility of dry matter, and feed efficiency as study outcomes. Feeding of Indigofera sp. and Pennisetum purpureum cv Mott in different doses significantly affected (p<0.05) dry matter digestibility, dry matter intake, daily weight gain and feed efficiency. In all variables, T2 significantly affected (p<0.05) all study outcomes compared to T1 and T0. Mean dry matter digestibility ranged from 41.5 to 65.0%. Mean dry matter intake ranged from 260.2 to 466.6 g/head/day. Mean daily weight gain ranged from 22.30 to 72.4 g/head/day. Mean feed efficiency in this study ranged from 22.30 to 72.4 g/head/day. We found an optimal response of goat after feeding with 60% Pennisteum purpureum cv. Mott + 40% Indigofera sp.